THE ROLE OF TEAM PLAYER ATTITUDES IN ENHANCING COLLABORATION IN MANUFACTURING FIRMS - Amborowati, Agustin; Novianto , Irfan (Jurnal Manajemen Bisnis dan Terapan, 2024)
This research aims to analyze the role of team player attitudes of PT XYZ, a garment manufacturing company. The importance of leadership in managing human resources and improving company performance. This research focuses on the role of team player attitudes which are considered crucial in achieving company goals. The research method used was a survey method by distributing questionnaires to 193 employees and 22 leaders in Manufacturing Companies. The majority of respondents were women in the productive age range and high school/vocational school education levels. The data obtained from the questionnaire was analyzed descriptively on the role of team player attitudes at PT XYZ. The research results show that most employees are satisfied with the existing teamwork, but prefer to work individually. This research can also be a reference for further research on leadership, especially in the context of garment manufacturing companies.